Effects on upper airway collapsibility of presence of a pharyngeal catheter - Maddison, K.; Shepherd, K.; Baker, V.; Lawther, B.; Platt, P.; Hillman, D.; Eastwood, Peter; Walsh, J. (Blackwell Publishing Ltd, 2015)
Summary: Catheters that traverse the pharynx are often in place during clinical or research evaluations of upper airway function. The purpose of this study was to determine whether the presence of such catheters affects measures of upper airway collapsibility itself. To do so, pharyngeal critical closing pressure (Pcrit) and resistance upstream of the site of collapse Rus) were assessed in 24 propofol-anaesthetized subjects (14 men) with and without a multi-sensor oesophageal catheter (external diameter 2.7 mm) in place. Anaesthetic depth and posture were maintained constant throughout each study. Six subjects had polysomnography(PSG)-defined obstructive sleep apnea (OSA) and 18 either did not have or were at low risk of OSA. Airway patency was maintained with positive airway pressure. At intervals, pressure was reduced by varying amounts to induce varying degrees of inspiratory flow limitation. The slope of the pressure flow relationship for flow-limited breaths defined Rus. Pcrit was similar with the catheter in and out (-1.5 ± 5.4 cmH2O and -2.1 ± 5.6 cmH2O, respectively, P = 0.14, n = 24). This remained the case both for those with PSG-defined OSA (3.9 ± 2.2 cmH2O and 2.6 ± 1.4 cmH2O, n = 6) and those at low risk/without OSA (-3.3 ± 4.9 cmH2O and -3.7 ± 5.6 cmH2O, respectively, n = 18). Rus was similar with the catheter in and out (20.0 ± 12.3 cmH2O mL-1 s-1 and 16.8 ± 10.1 cmH2O mL-1 s-1, P = 0.22, n = 24). In conclusion, the presence of a small catheter traversing the pharynx had no significant effect on upper airway collapsibility in these anaesthestized subjects, providing reassurance that such measures can be made reliably in their presence.